The Nottingham corpus of early modern German midwifery and women's medicine (ca. 1500-1700) - Whitt, Richard J. (University of Oxford Oxford Text Archive, 2016)
The Nottingham Corpus of Early Modern German Midwifery and Women’s Medicine (ca. 1500-1700), or the GeMi Corpus, is a collection of digitised, machine-readable text extracts from sixteenth- and seventeenth-century German-language medical texts devoted to midwifery and women’s medicine. The aim of the corpus is to provide a representative sample of the earliest printed German-language Fachsprache, or specialised language, devoted to midwifery and childbirth. Texts are available in two formats: as an untagged diplomatic transcription (the 'raw' version), and as an XML-encoded version (the 'TEI' version).